KELIMPAHAN BINTANG LAUT MAHKOTA DURI (Acanthaster planci L.) DI TELUK TOMINI, SULAWESI TENGAH - Preis Fransiska Malino; Annawaty Annawaty (Biocelebes, 2020)
This study was aimed to determine the abudance crown of thorn starfish (Acanthaster planci L.) in the Gulf of Tomini, Central Sulawesi. The study was conducted in February─April 2019 preliminary method used a purposive sampling (determining the sampling point for transect sampling) and the belt transect method which is 20 x 2 m. Sampling of A. planci was carried out at 4 stations. Data collected were the number of individuals, measurement of environmental parameters including Temperature, pH, Salinity, DO and Substrate observations on habitat. Based on the results of the study, 48 individuals at all stations and the abundance of A. planci in the Gulf of Tomini, Central Sulawesi were in the natural/normal category with a value of 0.01 ind/m2─0.25 ind/m2.